2012
DOI: 10.1186/1687-1499-2012-291
|View full text |Cite
|
Sign up to set email alerts
|

Energy allocation for green multiple relay cooperative communication

Abstract: Cooperative communication achieves diversity through spatially separated cooperating nodes, which are battery powered in most applications. Therefore the energy consumption must be minimized without compromising the quality of service. In this context, we present a novel energy allocation scheme for multiple relay nodes that results in efficient cooperative multiple-input multiple-output (MIMO) communication. Considering channel path loss, the total transmission energy is distributed between the source and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Previously it was demonstrated that in terms of network reliability and transmission energy multiple-relay system can outperform a single relay system without affecting the BER. [13]. A clear study has been demonstrated in [7]- [14], where performance on text message transmission was evaluated based on a single relay cooperative OFDM system under AF and DF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously it was demonstrated that in terms of network reliability and transmission energy multiple-relay system can outperform a single relay system without affecting the BER. [13]. A clear study has been demonstrated in [7]- [14], where performance on text message transmission was evaluated based on a single relay cooperative OFDM system under AF and DF.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, [15] has shown that BER was considerably improved by using multiple relays with low SNR value for audio and text data. Based on current wireless standards, such as IEEE 802.16j, in [8][9][10][11][12][13][14][15][16] an OFDM based multi-hop relaying system has been proposed. The issues with implementation of cellular network based on OFDM-based multi-hop was accounted by Can et al [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we assume the same system model [32][33][34][35] assumptions made in [25] i.e., we consider the source, destination and the relay terminals are equipped with a single antenna and the channels are assumed to be mutually independent. There are two phases of transmission in the cooperative communication system.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the equal energy allocation for all nodes in the network may not be optimal since the energy allocation at each node depends on many factors, such as the role of node (source and/or relay and/or destination), the location of node, and the connections of a node with the other nodes in the topology [28]. It is assumed that the energy supply of all nodes can be adaptively adjusted in a centralised manner to meet the total energy consumption constraint in the whole network.…”
Section: ) Total Available Energymentioning
confidence: 99%
“…It can be observed from (32) and (33) that, subject to fixed SNR of the wireless link and limited node power, we cannot allocate high data flows for wireless links in the non-NC-based LCRT protocol. However, in the proposed NC-based LCRT protocol, the summation of flows in the wireless link capacity and node energy constraints is replaced by the maximum of flows (see (28) and (30)). This means that, as |S m | is large, much higher data flows can be allocated for wireless links, and thus the system throughput is significantly improved.…”
Section: Cross-layer Designmentioning
confidence: 99%